The Development of P5 Interactive Module Based on Sumbawa Local Wisdom in the Implementation of Merdeka Curriculum - Suryani, Erma; Nurhairunnisah (Universitas Negeri Semarang, 2024)
This study aims to develop an interactive printed module based on Sumbawa local wisdom in order to support the implementation of the Merdeka Curriculum, especially in the Pancasila student profile strengthening project (P5) as an alternative teaching material for social studies teachers in remote areas of Batulante. Sumbawa local wisdom was chosen to provide culturally and contextually relevant content, thereby improving students' understanding of the teaching material. The research method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study only uses three stages. The first stage is an analysis of the needs for teaching materials in remote areas. The second stage is the design and development of the module involving education experts and practitioners in the field. The implementation of the module was carried out in several schools in Batulante by involving social studies teachers as trial subjects. Data were collected through observation, interviews, and teacher and student satisfaction questionnaires on the module used. The results of the study indicate that this P5 interactive printed module is suitable for use by teachers in the learning process and strengthens their understanding of social studies concepts associated with local wisdom values. The results of the validation of the Material expert with a score of 89.32% in the very valid category. Furthermore, the results of the validation of the Media expert with a score of the Valid Category and the last is the validation result by the Social Studies teacher with an average score of 84.68% in the Very Valid Category. The trial by the teacher obtained an average of 95% with a very good category and the student response obtained an average of 78% with a good category. The results of the study on the description of the descriptions of the Teachers who use this module feel more helped in delivering material in accordance with the Merdeka Curriculum, especially in the context of remote areas. This module is also considered effective in bridging the limitations of technological infrastructure in the Batulante area.